Kompetensi Pedagogik Guru dalam Membuat Rencana Pelaksanaan Pembelajaran di Taman Kanak-Kanak - Herlina Herlina (Journal of Educational Research, 2022)
This research aims to; find out how the pedagogic competence of teachers in making lesson plans, the efforts they make to improve pedagogic competence in making lesson plans, and identify inhibiting and supporting factors for teachers in making plans for implementing learning in Insan Kamil Kindergarten, Sekernan District. This research is a qualitative research with data collection techniques using observation, interviews and documentation. The results of the study indicate that pedagogic competence have not been met, including; the teachers have been able to make lesson plans but are still not perfect, the implementation of learning is still not in line with the RPPH, and there is no assessment of children's development. Efforts made by teachers to improve pedagogic competence include; (1) continue education at the S1 PAUD level, (2) participate in training, GTK PAUD tiered education, (3) attend meetings at PKG PAUD, (4) work together to make RPP. The supporting factors for increasing teacher pedagogic competence include; available facilities and infrastructure, background or age of participants, and teacher creativity. While the inhibiting factors include; teachers' pedagogic competence is still low and children's abilities are different. Penelitian ini bertujuan untuk; mengetahui bagaimana kompetensi pedagogik guru dalam membuat rencana pelaksanaan pembelajaran, upaya yang mereka lakukan untuk meningkatkan kompetensi pedagogik dalam membuat rencana pelaksanaan pembelajaran, dan mengidentifikasi faktor penghambat dan pendukung bagi Guru dalam membuat rencana pelaksanaan pembelajaran di taman kanak-kanak Insan Kamil Kecamatan Sekernan. Penelitian ini adalah penelitian kualitatif dengan teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan adanya indikator kompetensi pedagogik yang belum terpenuhi antara lain; rencana pembelajaran namun masih belum sempurna, pelaksanaan pembelajaran yang masih belum selaras dengan RPPH, dan tidak adanya penilaian terhadap perkembangan anak. Upaya yang dilakukan guru untuk meningkatkan kompetensi pedagodik antara lain; (1) melanjutkan pendidikan kejenjang S1 PAUD, (2) mengikuti pelatihan, Diklat berjenjang GTK PAUD, (3) Mengikuti pertemuan di PKG PAUD, (4) Bekerja sama untuk membuat RPP. Adapun faktor pendukung peningkatan kompetensi pedagogik guru antara lain; tersedia sarana dan prasarana, latar belakang atau usia peserta, dan kreatifitas guru. Sedangkan faktor penghambatnya berupa; kompetensi pedagogik guru yang masih rendah dan kemampuan anak yang berbeda-beda.